Visually guided saccades and acoustic distractors: no evidence for the remote distractor effect or global effect - Tari, B; Tremblay, L; Heath, M (Springer Nature, 2020)
A remote visual distractor increases saccade reaction time (RT) to a visual target and may reflect the time required to resolve conflict between target- and distractor-related information within a common retinotopic representation in the superior colliculus (SC) (i.e., the remote distractor effect: RDE). Notably, because the SC serves as a sensorimotor interface it is possible that the RDE may be associated with the pairing of an acoustic distractor with a visual target; that is, the conflict related to saccade generation signals may be sensory-independent. To address that issue, we employed a traditional RDE experiment involving a visual target and visual proximal and remote distractors (Experiment 1) and an experiment wherein a visual target was presented with acoustic proximal and remote distractors (Experiment 2). As well, Experiments 1 and 2 employed no-distractor trials. Experiment 1 RTs elicited a reliable RDE, whereas Experiment 2 RTs for proximal and remote distractors were shorter than their no distractor counterparts. Accordingly, findings demonstrate that the RDE is sensory specific and arises from conflicting visual signals within a common retinotopic map. As well, Experiment 2 findings indicate that an acoustic distractor supports an intersensory facilitation that optimizes oculomotor planning.